Systematic evaluation of the aggregate types and properties on metakaolin based geopolymer composites - Sahin, Furkan; Uysal, Mucteba; Canpolat, Orhan (ELSEVIER SCI LTD, 2021)
Although aggregates constitute the largest volume in geopolymer composites, there are limited studies related to this parameter. This study investigates the effect of different types of aggregates on the mechanical and durability properties of metakaolin (MK) based geopolymer composites. For this study, while using metakaolin as the main raw material, slag (S) was used to gain an early setting. Six different sand types (silica sand, river sand, sandstone, Rilem sand, waste concrete aggregate, and basalt sand) were used in the geopolymer mortar. The ultrasonic pulse velocity (UPV) and flexural and compressive strength results of 7, 28, and 56 days were found to examine the effect of aggregates, while the unit weight, voids ratio, water absorption, and workability properties of the samples were also investigated. XRD analyzes were performed for the crystalline materials' structure. After 56 days, the samples were exposed to 180 cycles of the freezing-thawing test (1 cycle consists of 12 h at -18 degrees C and 12 h at +4 degrees C) and high temperatures of 200, 400, 600, and 800 degrees C. After the tests, UPV and strength results were found and weight changes were also examined. Also, an abrasion test was applied. SEM analyzes were carried out pre and post the high-temperature test. Test results have shown that basalt sand added samples produced better results due to their more dense and compact structure compared to other aggregates. Similarly, high results were obtained by using silica sand and sandstone. In the case of using waste concrete aggregate, it was seen that acceptable results were obtained in terms of structural features. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer; Metakaolin; Waste concrete aggregate; Basalt sand; Silica sand; Sandstone; High temperature; Freezing-thawing; Construction & Building Technology; Engineering; Materials Science